Correlation of Radiomorphometric Indices of the Mandible and Biochemical Parameters in Patients with Secondary Hyperparathyroidism Due to Chronic Kidney Disease - Queiroz, Stenio Medeiros; Andrade, Ana Luiza Dias Leite De; Oliveira, Patrícia Teixeira De; Leite Maia, Paulo Raphael; Oliveira, Ângelo Giuseppe Roncalli Da Costa; Almeida Freitas, Roseana De; Galvão, Hébel Cavalcanti (European Journal of Dentistry, 2019)
Objective The aim was to correlate radiomorphometric indices and biochemical analyses as an auxiliary method in bone evaluation in male and female patients with chronic kidney disease–mineral and bone disorder (CKD-MBD) and controls.Materials and Methods Nine radiomorphometric indices and four biochemical parameters were obtained: mental index (MI), height at the mental foramen, total mandibular height (THM), panoramic mandibular index (PMI), original height of the mandible, alveolar bone resorption, distance from the mental foramen to the alveolar bone crest (MF-ABC), mandibular cortical index (MCI), trabecular bone pattern, parathyroid hormone (PTH), calcium (Ca), phosphorus (P), and Ca × P product (Ca × P).Statistical Analysis The Mann–Whitney U-test, chi-squared test, and Spearman’s correlation were applied at a significance level of 95%.Results There was a moderate negative and significant correlation between MI, PMI, and PTH in female patients with CKD-MBD as well as between THM, MF-ABC, and Ca × P. The MCI and trabecular bone pattern indicated altered bone quality in male patients.Conclusions The radiomorphometric evaluation was an auxiliary, noninvasive method to detect possible alterations in the cortex and mandibular bone trabeculation in male and female patients with CKD-MBD.
Keywords: chronic kidney disease; panoramic radiography; radiomorphometric indices; renal osteodystrophy; secondary hyperparathyroidism